Early signs of sleep-disordered breathing in healthy women predict carotid intima-media thickening after 10 years - Kalleinen Nea; Saaresranta Tarja; Polo Olli; Raitakari Olli T; Riskumäki Markus; Vahlberg Tero; Aittokallio Jenni (ELSEVIER, 2022)
Background: Cardiovascular disease (CVD) is the leading cause of death in women. The risk of CVD increases in women after menopause. The aim was to study how sleep parameters and cardiovascular risk factors in 46-year-old women predict future carotid intima-media thickness (IMT) 10 years after.
Methods: Prospective study of 92 healthy women, aged 46 years, were studied at baseline and at 10-year follow-up. Polysomnography for sleep and breathing; blood samples for cholesterol, glucose and follicle stimulating hormone; blood pressure (BP), weight and height measurements; questionnaires for background variables and vasomotor symptoms were carried out at both time points. Carotid ultrasound was scanned for IMT at 10-year follow-up.
Results: After adjusting for conventional risk factors, apnea-hypopnea index (AHI) during rapid-eye movement (REM) sleep was the only parameter at baseline that predicted IMT 10 years after (IMT mean: 13 81.4 [95% CI, 14.0-148.8]; IMT max: 13 104.7 [95% CI, 15.4-194.1]). At 10-year follow-up, higher arousal index (IMT mean: 13 55.6 [95% CI, 19.5-91.8]; IMT max 13 59.9 [95% CI, 11.4-108.4]) and lower vasomotor symptoms (IMT max: 13-60.5 [95% CI,-119.0 to-2.0]) were associated with concurrent higher IMT. The conventional risk factors at baseline did not associate with future IMT but 10 years after higher concurrent HbA1c (IMT mean: 13 11.0 [95% CI, 3.4-18.5]; IMT max 13 14.0 [95% CI, 4.1-23.8]) and systolic BP (IMT mean: 13 2.4 [95% CI, 1.1-3.7]; IMT max: 13 2.7 [95% CI, 1.03 to 4.53]) were associated with higher IMT.
Conclusions: In healthy 46-year-old women, AHI during REM sleep predicted IMT 10 years after. The conventional risk factors (HbA1c and BP) only associated with the concurrent IMT at 10-year follow-up. (c) 2022 The Authors. Published by Elsevier B.V. This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/4.0/).